Diversidad y Biomasa Arbórea en los Bosques Andinos del Santuario Nacional del Ampay, Apurímac – Perú: Diversity and Arboreal Biomass in the Andean Forests of the Ampay National Sanctuary, Apurímac – Perú - Huamantupa Chuquimaco, Isau (2019)
ResumenEn los bosques andinos del Santuario Nacional del Ampay en el sur peruano, se evaluó la diversidad y biomasa arbórea de cuatro parcelas permanentes de 60 m x 60 m. Se registraron 1920 individuos de plantas leñosas con DAP ≥ 5 cm, pertenecientes a 35 especies, 27 géneros y 20 familias. Las especies más abundantes fueron Podocarpus glomeratus, Hesperomeles gayana y Verbesina sp.2, que concentraron más del 56 % del total. Las parcelas PBA-3 y PBA-4 fueron las más diversas con 20 especies. La estructura del bosque muestra que árboles con tallos delgados (5 a 15 de DAP), son dominantes. La biomasa aérea total fue de 135.40/141.49 (t haˉ¹), de estas la parcela PBA-3 registró mayor biomasa con 52.14/52.54 (t haˉ¹), P. glomeratus tuvo mayor aporte de biomasa con 100.28/104.90 (t haˉ¹), seguidas de Vallea stipularis con 8.35/8.97 (t haˉ¹) y Hesperomeles gayana con 3.40/3.78 (t haˉ¹). Son notablemente de baja diversidad y riqueza comparadas a otros lugares con similares altitudes como los bosques montanos de las vertientes orientales de los andes y los patrones de diversidad y biomasa aérea se asemejan a otros bosques andinosprincipalmente a las cuencas de ecosistemas secos del Urubamba y Paucartambo. Pero los bosques del SNA son particulares por su composición y estructura caracterizados por la dominancia de la “intimpa” Podocarpus glomeratus que a pesar de estar protegidos necesitan urgentemente de más esfuerzos de conservación por parte de la población local y autoridades del SNA que conlleven a reducir los impactos negativos vinculados a las actividades antrópicas. AbstractIn the Andean forests of the National Sanctuary of Ampay in southern Peru, the diversity and arboreal aerial biomass of four permanent plots of 60 m x 60 m were evaluated. We recorded 1920 individuals of woody plants with DBH ≥ 5 cm, belonging to 35 species, 27 genera and 20 families. The most abundant species were Podocarpus glomeratus, Hesperomeles gayana and Verbesina sp.2, which accounted for more than 56% of the total. Plots PBA-3 and PBA-4 were the most diverse with 20 species. The forest structure shows that trees with thin stems (5 to 15 DAP) are dominant. The total aerial biomass was of 135.40 / 141.49 (t haˉ¹), of these the plot PBA-3 registered greater biomass with 52.14 / 52.54 (t haˉ¹), P. glomeratus had greater -contribution of biomass with 100.28 / 104.90 (t haˉ¹), followed by Vallea stipularis with 8.35 / 8.97 (thaˉ¹) and Hesperomeles gayana with 3.40 / 3.78 (t haˉ¹). They are remarkably low in diversity and richness compared to other places with similar altitudes as the montane forests of the eastern slopes of the Andes and the patterns of diversity and aerial biomass resemble other Andean forests mainly to the dry ecosystem basins of the Urubamba and Paucartambo. But the SNA forests are particular for their composition and structure characterized by the dominance of the "intimpa" Podocarpus glomeratus that despite beingprotected urgently need more conservation efforts by the local population and authorities of the NSA that lead to reduce the negative impacts linked to anthropic activities.